2017
DOI: 10.3390/aerospace4030042
|View full text |Cite
|
Sign up to set email alerts
|

A Concept for Multi-Criteria Environmental Assessment of Aircraft Trajectories

Abstract: Comprehensive assessment of the environmental aspects of flight movements is of increasing interest to the aviation sector as a potential input for developing sustainable aviation strategies that consider climate impact, air quality and noise issues simultaneously. However, comprehensive assessments of all three environmental aspects do not yet exist and are in particular not yet operational practice in flight planning. The purpose of this study is to present a methodology which allows to establish a multi-cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 44 publications
6
48
0
Order By: Relevance
“…In the operational field, the study of the optimal trajectory has been broadly researched [69][70][71], in most of the cases linked to FCO. The FCO in the air transport sector is an old topic [72], and aside from the obvious business interests, sustainability is making it again a trending topic [73][74][75][76]. (c)…”
Section: (B)mentioning
confidence: 99%
“…In the operational field, the study of the optimal trajectory has been broadly researched [69][70][71], in most of the cases linked to FCO. The FCO in the air transport sector is an old topic [72], and aside from the obvious business interests, sustainability is making it again a trending topic [73][74][75][76]. (c)…”
Section: (B)mentioning
confidence: 99%
“…Within a simple framework the trade-off between the climate impact of CO 2 emissions 2 of 15 and contrails for a single flight were assessed [2,3]. More comprehensive studies showed the feasibility of climate-optimized trajectories with single day case studies in order to reduce total climate impact of aviation in the North Atlantic Flight corridor [4] and over Europe [5]. A more recent study focused on the mitigation of contrail effects when considering trade-offs in CO 2 [6].…”
Section: Introductionmentioning
confidence: 99%
“…AirTraf can take into account where and when aviation emissions are released or contrails form. The road map for our overall study has been shown elsewhere (Grewe et al, 2017b;Matthes et al, 2017). This paper presents a technical description of AirTraf (version 2.0).…”
mentioning
confidence: 99%